Evolution of dengue vírus in Ecuador 2000-2015 - Real-Cotto, Jhony Joe (2017)
Introduction: Nowadays, the dengue virus infection is one of the most important arboviroses in the world’s tropical and subtropical regions. Objective: To determine the evolution of the dengue virus circulating in Ecuador during the period 2000-2015. Design: Non-experimental, transversal, descriptive and correlational study. Setting: Health units of Ecuador. Participants: The samples were taken from dengue suspects with less than 5 days from the beginning of the disease. Results: In 2000, the four serotypes were present, with prevalence of DEN3 during 2001-2006 coinciding with the increase of cases in 2000, 2001 and 2005; in 2004, the DEN1 virus reappeared and, during the following years, its presence predominated between 2007 and 2012, coinciding with the increase of cases in 2010. From 2011 to 2015 three circulating viruses were present at the same time (DEN1, DEN2 and DEN4); in 2014 and 2015, the DEN3 virus predominated; the predominance of the DEN2 virus was in 2013 and 2014, and of the DEN1 virus in 2015. The province of Guayas had the greatest relation with the virus. Conclusions: The presence and permanence of several serotypes of dengue virus circulating at the same time is due to other factors influencing the virus behavior and variability of the four serotypes. The molecular surveillance of the circulating serotypes, genotypes and dengue virus lineages should be strengthened.